2019
DOI: 10.3389/fpubh.2019.00177
|View full text |Cite
|
Sign up to set email alerts
|

Keeping Bystanders Active: Resuscitating Resuscitation Skills

Abstract: Introduction: Sufficient CPR skills in the general population are essential to make them active bystanders and contribute to an effective chain of survival in cardiac arrest emergencies. However, having a large proportion of the population regularly retrained is practically infeasible. Objective: The aim of this study was to assess and retrain cardiopulmonary resuscitation (CPR) skills of individuals who received (limited) CPR training several months to years prior. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
2
0
2

Year Published

2020
2020
2023
2023

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 17 publications
0
2
0
2
Order By: Relevance
“…The same research showed that the quality performance of the CPR procedure increased incredibly after watching a six-minute video with instructions and performing the practical part. With this procedure, as many as 96% of respondents met the level of performance specified in the Guidelines [7]. In this study, 85% of the students who previously attended health-oriented secondary school took part, and they, apart from taking the driving test, also encountered the BLS procedure and CPR procedures through secondary education.…”
Section: Discussionmentioning
confidence: 75%
See 3 more Smart Citations
“…The same research showed that the quality performance of the CPR procedure increased incredibly after watching a six-minute video with instructions and performing the practical part. With this procedure, as many as 96% of respondents met the level of performance specified in the Guidelines [7]. In this study, 85% of the students who previously attended health-oriented secondary school took part, and they, apart from taking the driving test, also encountered the BLS procedure and CPR procedures through secondary education.…”
Section: Discussionmentioning
confidence: 75%
“…The survey showed that a large percentage of respondents (92%) have a driver's license, confirming that all respondents (100%) were familiar with BLS. However, given that it is known that the skills and knowledge of BLS and CPR that are acquired during certain trainings are reduced and forgotten over time, it has been proven that one training of the mentioned programs is not enough for long-term competence [7]. The same has been proven with medical professionals, where it has been established that the quality of performance of the exact procedures usually deteriorates in the first year after certification [8].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations